Experimental study on gas production from methane hydrate in porous media by SAGD method - Li, Xiao-Sen; Yang, Bo; Duan, Li-Ping; Li, Gang; Huang, Ning-Sheng; Zhang, Yu (Applied Energy, 2013)
A 117.8 L three-dimensional pressure vessel is used to study the methane hydrate dissociation with the steam assisted gravity drainage (SAGD) method. It is called the Pilot-Scale Hydrate Simulator (PHS). This study proposes the evaluation and the comparisons of the gas production performance by SAGD method from the methane hydrate reservoir with different steam injection rates. It indicates that the experiment could be divided into three main stages: the original gas releasing stage, the original and the hydrate-originating gas releasing stage, and the hydrate-originating gas releasing stage (the SAGD process). Furthermore, the temperature change consists of the four periods: decreasing dramatically, keeping stable, rising gradually, and keeping steady. With the injected steam flowing downwards and sideways, the steam chamber is expanding. The gas production rate increases with the steam injection rate, while the Energy Efficiency Ratio (EER) and gas-to-water ratios are improved by the decrease of the steam injection rate. (C) 2013 Elsevier Ltd. All rights reserved.